Excessive Object Attachment in Hoarding Disorder: Examining the Role of Interpersonal Functioning. Issue 5 (September 2021) - David, Jonathan; Aluh, Deborah O.; Blonner, Marika; Norberg, Melissa M.
Highlights: Excessive object attachment leads to difficulty discarding in hoarding disorder. We examined the impact of interpersonal functioning on object attachment. Interpersonal anxious attachment moderated object attachment levels across time. Empathy toward fictional characters and personal distress may play a role. Results suggest that hoarding disorder is likely not due to theory of mind problems. Abstract: Excessive attachment towards possessions can be maladaptive because it can lead individuals to excessively acquire and save objects. Little is known about how attachment to objects develops and changes over time; however, interpersonal factors have been theorized to play a role. The current study examined whether interpersonal factors, specifically interpersonal attachment style and empathy, moderate changes in object attachment over time. A total of 145 participants with excessive acquiring and discarding difficulties rated their level of attachment to a novel object just after receiving it, and 1 week later. Participants also completed measures of interpersonal anxious attachment and interpersonal functioning. We found that changes in object attachment over time were moderated by interpersonal anxious attachment. Also, our findings suggested that individuals with hoarding problems are likely not impaired in their ability to empathize with others, but rather have difficulty displaying empathy in tense social situations and also have more empathy for fictional characters. Further, greater discomfort in tense social situations and greater empathy for fictional characters interacted to predict greater object attachment. Taken together, these findings indicate that individuals with an interpersonal anxious attachment style may be those at risk of forming greater attachments to objects over time. A learning history that includes inconsistent support from caregivers may result in individuals experiencing more empathy for fictional characters and discomfort in tense social situations, which may produce a vulnerability for becoming excessively attached to objects. Our results are in line with theories of hoarding which propose that individuals use objects to compensate for unmet interpersonal needs and suggest that treatment may need to target interpersonal functioning to reduce hoarding symptoms.